Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.3390/horticulturae8030239
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review on Amaranthus-Related Research

Abstract: Leafy vegetables promote reparation of energy loss due to oxidative stress, and they have the potential to alleviate hunger and malnutrition as well as other forms of metabolic imbalance ravaging the world. However, these vegetables are underutilized, despite the fact that they harbor essential minerals needed for critical cellular activities. As amaranth is one of the earliest vegetables reputed for its high nutraceutical and therapeutic value, in this study, we explored research on the Amaranthus species, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 118 publications
(171 reference statements)
0
2
0
Order By: Relevance
“…Jimoh et al [ 48 ] reviewed on Amaranthus-Related Research extensively. Rodríguez-Ríos et al [ 49 ] fed autoclaved amaranth at levels of 15, 30 and 45% and concluded that the use of a 15% level of amaranth can lead to maintained production performance, which is in agreement with the present study (the type and level amaranth section).…”
Section: Discussionmentioning
confidence: 99%
“…Jimoh et al [ 48 ] reviewed on Amaranthus-Related Research extensively. Rodríguez-Ríos et al [ 49 ] fed autoclaved amaranth at levels of 15, 30 and 45% and concluded that the use of a 15% level of amaranth can lead to maintained production performance, which is in agreement with the present study (the type and level amaranth section).…”
Section: Discussionmentioning
confidence: 99%
“…65,66 Amaranth leaves should be grown in households around the world as a vegetable due to its resilience under many climatic conditions, and amaranth grain cultivation may be expanded worldwide since the gluten problem (from wheat, rye, and barley) has become better known. 67 According to a review done to suggest amaranth green as a suitable home garden vegetable for peoples worldwide to encourage more consumption of vegetables. 68 Amaranth has additionally been associated with a range of health advantages, including reduced cholesterol, less inflammation, and faster weight loss.…”
Section: Dovepressmentioning
confidence: 99%
“…On the other hand, several species of the genus Amaranthus are traditionally cultivated in Central and South America, where local people use seeds or leaves as food and herbal remedies [80]. Therefore, the traditional uses of A. caudatus, A. cruentus, A. hybridus, and A. quitensis deserve to be validated with scientific evidence to enhance their sustainable use as a food supplement or in phytopharmaceutical products.…”
Section: Malvaceaementioning
confidence: 99%